Kinetic investigation of plasma catalytic synthesis of ammonia: insights into the role of excited states and plasma-enhanced surface chemistry. (1st September 2022) - Sun, Jintao; Chen, Qi; Zhao, Xuteng; Lin, He; Qin, Wanyue
Abstract: The present work investigates the kinetics of catalytic ammonia synthesis in a N2 /H2 mixture activated by a nanosecond pulsed discharge plasma experimentally and numerically. X-ray diffraction, high-resolution transmission electron microscopy and x-ray photoelectron spectroscopy are combined to characterize the morphology and surface electronic properties of the catalyst. Special attention is placed on the role of excited species in promoting the formation of important intermediates and the plasma-enhanced surface chemistry. A detailed kinetic mechanism consisting of atoms, radicals, excited species, molecules, ions, and surface species is developed and studied by incorporating a set of the electron impact reactions, reactions involving excited species, ionic reactions, direct and dissociative adsorption reactions, and surface reactions. A zero-dimensional model incorporating the plasma kinetics solver is used to calculate the temporal evolution of species densities in a N2 /H2 plasma catalysis system. The results show that the coupling of Fe/γ–Al2 O3 catalyst with plasma is much more effective in ammonia synthesis than the Fe/γ–Al2 O3 catalyst alone and plasma alone. The numerical model has a good agreement with experiments in ammonia formation. The path flux analysis shows the significant roles of excited species N( 2 D), H2 (v1), N2 (v) in stimulating the formation of precursors NH, NH2, and adsorbed N(s) through the pathways N( 2 D) + H2 → NH + H, H2 (v1) + NH → NH2 + H and N2 (v) + 2Fe(s) → N(s) + N(s), respectively. Furthermore, the results show that the adsorption reaction N + Fe(s) → N(s) and Eley–Ridel interactions N(s) + H → NH(s), N + H(s) → NH(s), NH + H(s) → NH2 (s) and NH2 + H(s) → NH3 (s) can kinetically enhance the formation of ammonia, which further highlights the plasma-enhanced surface chemistry. This work provides new insights into the roles of excited species and plasma-enhanced surface chemistry in the plasma catalytic ammonia synthesis.